Short Medical Missions During Wartime: The Sudanese American Medical Association’s Experience in Sudan in 2024 - Mohamed Almahal; Mohamed Ahmed; Omer Abdalla; Omnia Sharef; Salaheldin Abusin; Yasir Hamad; Amir Elhassan; Sami Abd Elwahab (Sudan Journal of Medical Sciences, 2025)
Background: The armed conflict that erupted in Sudan in April 2023 has severely disrupted the country’s healthcare system, displacing millions and straining the already fragile health infrastructure. Port Sudan, now functioning as the de facto capital, has experienced a significant population surge. In response, the Sudanese American Medical Association (SAMA) launched a series of short-term humanitarian medical missions in 2024 to support local healthcare delivery. This article outlines the implementation and key activities of these missions, including medical supply delivery and healthcare provider training.